2017
DOI: 10.1016/j.btre.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of petroleum oil biodegradation by a consortium of three protozoan isolates ( Aspidisca sp., Trachelophyllum sp. and Peranema sp.)

Abstract: HighlightsThere was an increase in the percentage removal of petroleum oil in low concentrations.There was a reduction of 45% and 78% for petroleum concentrations of 250 mg/L and 50 mg/L, respectively in glucose-supplemented culture media.Biodegradation of between 33 and 90% was achieved at a Tween® 80 concentration.The highest efficiency of ≥20% of Tween® 80 was observed between 6 and 18 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 24 publications
(36 reference statements)
4
13
0
Order By: Relevance
“…Degradation decreased with increasing concentration perhaps due to the toxicity of the crude oil in the medium (Farag et al, 2018). A similar finding was also reported by Kachieng and Momba (2017). Dibble and Bartha (1979) reported increases in biodegradation as indicated by increases in CO2 evolution in soil polluted with 5% crude oil.…”
Section: Effect Of Crude Oil Concentration On Biodegradation Of Bonnysupporting
confidence: 83%
“…Degradation decreased with increasing concentration perhaps due to the toxicity of the crude oil in the medium (Farag et al, 2018). A similar finding was also reported by Kachieng and Momba (2017). Dibble and Bartha (1979) reported increases in biodegradation as indicated by increases in CO2 evolution in soil polluted with 5% crude oil.…”
Section: Effect Of Crude Oil Concentration On Biodegradation Of Bonnysupporting
confidence: 83%
“…Thus, rate constant was the highest in consortium 3 (1.713 day −1 , t 1/2 = 0.404) followed by consortium 2 (1.469 day −1 , t 1/2 = 0.463) and consortium 1 (0.653 day −1 , t 1/2 = 1.06) in a decreasing order. Kachieng'a and Momba [41] reported that the highest rate constant of 1.11 day −1 was observed for a consortium consisting of three different protozoa. In a similar study, the reaction rate constants of Pseudomonas pseudoalcaligenes, Bacillus megaterium and Xanthobacter autotrophicus were 0.0189, 0.0324 and 0.0324 day −1 , respectively.…”
Section: Evaluation Of Growth Intensities and Petroleum Biodegradatiomentioning
confidence: 98%
“…The kinetics of biodegradation processes depend on the rate and improvement in the effective degradation of petroleum [41]. According to biodegradation efficiencies of consortia, the specific degradation rates of consortium 1, consortium 2 and consortium 3 were 0.068, 0.110 and 0.117, per day, respectively.…”
Section: Evaluation Of Growth Intensities and Petroleum Biodegradatiomentioning
confidence: 99%
“…The growth of microorganisms in stressful conditions can be stimulated by addition of easily assimilated carbon and nitrogen sources 8 . Bioremediation offers benefits such as economy, reliability and eco-friendly nature over the physicochemical methods 9 .…”
Section: Introductionmentioning
confidence: 99%